Insight into watery saliva proteomes of the grain aphid, Sitobion avenae. Issue 1 (20th October 2020) - Zhang, Yong; Fu, Yu; Francis, Frédéric; Liu, Xiaobei; Chen, Julian
Abstract: The grain aphid, Sitobion avenae, is an economically important cereal pest worldwide. Aphid saliva plays an essential role in the interaction between aphids and their host plants. However, limited information is available regarding the proteins found in the saliva of S. avenae . Here, the watery saliva proteins from S. avenae were collected in an artificial diet and identified using a liquid chromatography–mass spectrometry/mass spectrometry analysis. A total of 114 proteins were identified in S. avenae saliva, including several enzymes, binding proteins, and putative effectors, as well as other proteins with unknown functions. In comparison with salivary proteins from nine other aphid species, the most striking feature of the salivary protein from S. avenae was the different patterns of protein functions. Several orthologous proteins secreted by other aphid species such as glucose dehydrogenase, elongation factors, and effector C002 were also detected in S. avenae saliva and speculated to play a significant role in aphid–plant interactions. These results provide further insight into the molecular basis between aphids and cereal plant interactions. Abstract : The watery saliva of grain aphid Sitobion avenae was collected using an artificial diet. Then, the aphid salivary proteins were identified using liquid chromatography–mass spectrometry/mass spectrometry. A total of 114 salivary proteins were successfully identified in our study. Highlights: A total of 114 salivary proteins were identified from the watery saliva of Sitobion avenae using proteomics. Compared with the salivary proteins from other aphid species, some orthologous and species‐specific salivary proteins were identified.